Physical Exercise Enhanced Heat Shock Protein 60 Expression and Attenuated Inflammation in the Adipose Tissue of Human Diabetic Obese - Khadir, Abdelkrim; Kavalakatt, Sina; Cherian, Preethi; Warsame, Samia; Abubaker, Jehad Ahmed; Dehbi, Mohammed; Tiss, Ali (Frontiers in Endocrinology, 2018)
Heat shock protein 60 (HSP60) is a key protein in the crosstalk between cellular stress and inflammation. However, the status of HSP60 in diabetes and obesity is unclear. In the present study, we investigated the status of HSP60 in the adipose tissue of obese adults with and without diabetes and changes in its expression in response to a supervised 3-month physical exercise program. Subcutaneous adipose tissue (SAT) and blood samples were collected from obese adults with and without diabetes (n=138 and n=92, respectively, at baseline; n=43 for both groups after 3 months of physical exercise). Conventional RT-PCR, immunohistochemistry, immunofluorescence, and ELISA were used to assess the expression and secretion of HSP60. Compared to obese adults without diabetes, HSP60 mRNA and protein levels were decreased in SAT in obese adults with diabetes together with increased inflammatory and glycemic marker expression and lower fitness. More interestingly, moderate physical exercise differentially modulated HSP60 expression and the heat shock response but attenuated inflammation in both groups, as reflected by decreased endogenous levels of IL6 and TNF-α. Indeed, HSP60 expression levels in SAT were significantly increased by exercise in the diabetes group, whereas they were decreased in the non-diabetes group. These results were further confirmed using immunofluorescence microscopy. Despite its decreased secretion in obese adults with diabetes, exercise had only marginal effects on HSP60 secretion and HSP60 autoantibody levels in plasma. Physical exercise differentially alleviates cellular stress in obese adults with and without diabetes despite concomitant attenuation of the inflammatory response.